Implementation of Multi-literacy Education Based on Cultural Literacy with the TANDUR Strategy in Community Learning Center (CLC) - Krisna Kartika Pratiwi; Suhadjo Suhadjo; Bintoro Wibowo; Mita Lutviatiani (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
The needed for a grand design of education in the implementation of literacy education in order to provide an output in the form of a literate society and able to solve problems in their lives as expected by the law. No. 20 of 2003 article 3 which states that national education functions to develop capabilities and shape the character and civilization of the nation so that they are able to actively participate in advancing the world community. So, to be able to make it happen, the TANDUR strategy is a strategic solution for the implementation of literacy education. Development the implementation of multi-literacy education in Community Learning Center (CLC) or PKBM is carried out using the RnD method and the application of quasi-experiments to test the developed model. The results obtained in this study are the TANDUR strategy applied in the implementation of multi-literacy in Community Learning Center (CLC) has a positive effect, both on tutors, the learning process, and the learning community.